A novel rapid LAMP test for identification of cutaneous leishmaniasis: An evaluation and comparative analysis of three molecular methods. (August 2022) - Salari, Samira; Taghdiri, Ahmad; Bamorovat, Mehdi; Sharifi, Iraj; Ghasemi Nejad Almani, Pooya
Abstract: Leishmaniasis is a neglected and widespread parasitic disease that can lead to serious health problems. The conventional method in diagnostic health clinics is direct smear preparation of the lesion and staining with standard Giemsa to visualize the amastigote stage and by culturing the organism in an NNN (Novy-MacNeal-Nicolle) to observe the promastigote form of the parasite. In the case of urban-type leishmaniasis, microscopic diagnosis is sometimes not possible due to the reduction of amastigotes in patients' wounds. Because most endemic areas are located in regions that do not have access to laboratories equipped with molecular tools, access to a rapid test to diagnose the disease is essential. In this study, for the first time for DNA extraction, the scalpel used for sampling was washed and extracted by boiling method. Also, the LAMP technique in this study was modified so that the test can be performed in 10 min and the results can be recognized by color. We used four microscopic methods, conventional PCR, real-time PCR, and LAMP, to diagnose urban-type leishmaniasis and compared the results of these methods with each other. The sensitivity and specificity of LAMP were higher than other techniques used. Therefore, it allows rapid diagnosis for timely treatment of the disease to control the primary reservoir host more quickly in ACL as humans are the principal source of infection. This test is performed at a high-speed and is cost-effective. For its convenience, this test is highly recommended to be used in endemic areas. Graphical abstract: Image 1 Highlights: Leishmaniasis is a neglected and widespread parasitic disease that can lead to serious health problems. Most endemic areas do not have access to laboratories, access to a rapid test to diagnose the disease is essential. In this study, for DNA extraction, the scalpel used for sampling was washed and extracted by boiling method. The LAMP technique was modified so that the test can be performed in 10 min and the results can be recognized by color. This test is high-speed and cost-effective in terms of cost.